Searches for direct pair production of supersymmetric top and supersymmetric bottom quarks in pp̄ collisions at s=1.96TeV - Aaltonen, T; Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
We search for direct pair production of supersymmetric top quarks and supersymmetric bottom quarks in proton-antiproton collisions at s=1.96TeV, using 295pb-1 of data recorded by the Collider Detector at Fermilab (CDF II) experiment. The supersymmetric top (supersymmetric bottom) quarks are selected by reconstructing their decay into a charm (bottom) quark and a neutralino, which is assumed to be the lightest supersymmetric particle. The signature of such processes is two energetic heavy-flavor jets and missing transverse energy. The number of events that pass our selection for each search process is consistent with the expected standard model background. By comparing our results to the theoretical production cross sections of the supersymmetric top and supersymmetric bottom quarks in the minimal supersymmetric standard model, we exclude, at a 95% confidence level in the frame of that model, a supersymmetric top quark mass up to 132GeV/c2 for a neutralino mass of 48GeV/c2, and a supersymmetric bottom quark mass up to 193GeV/c2 for a neutralino mass of 40GeV/c2. © 2007 The American Physical Society.